ANALYSIS OF THE INFLUENCE OF APTITUDE AND ATTITUDE ON BURNOUT RATES AND WORK PERFORMANCE (LITERATURE REVIEW OF HUMAN RESOURCE MANAGEMENT) - Suwiknyo, Pangki (Dinasti International Journal of Digital Business Management, 2022)
This study aims to determine the influence of aptitude and attitude on burnout rates and work performance. This research is a case study in medical personnel at the Regional General Hospital (RSUD) of Sorong Regency. Aptitude and attitude are important factors for the performance of medical personnel in providing services to the patients. Exposure to patients with complex and persistent problems is believed to cause burnout in medical personnel. Burnout rates will be related to work performance in medical personnel. The purpose of writing this article is to build hypotheses that are useful for future research. This article reviews variables that affect burnout rates and work performance. The result of this library research article is that aptitude and attitude factors affect burnout rates and the work performance of medical personnel.